Bone resorption: supporting immunometabolism. (28th February 2018) - van Niekerk, Gustav; Mitchell, Megan; Engelbrecht, Anna-Mart
Abstract : Activation of the immune system is associated with an increase in the breakdown of various peripheral tissues, including bone. Despite the widely appreciated role of inflammatory mediators in promoting bone resorption, the functional value behind this process is not completely understood. Recent advances in the field of immunometabolism have highlighted the metabolic reprogramming that takes place in activated immune cells. It is now believed that the breakdown of peripheral tissue provides metabolic substrates to fuel metabolic anabolism in activated immune cells. We argue that phosphate, liberated by bone resorption, plays an indispensable role in sustaining immune cell metabolism. The liberated phosphate is then incorporated into macromolecules such as nucleotides and phospholipids, and is also used for the phosphorylation of metabolites (e.g. glycolytic intermediates). In addition, magnesium, also liberated during the breakdown of bone, is an essential cofactor required by various metabolic enzymes which are upregulated in activated immune cells. Finally, calcium activates various additional molecules involved in immune cell migration. Taken together, these factors suggest a key role for bone resorption during infection.